2011
DOI: 10.1159/000321593
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant Treatments Change 5-HT2C Receptor mRNA Expression in Rat Prefrontal/Frontal Cortex and Hippocampus

Abstract: Background/Aims: Compelling evidence would suggest the involvement of the serotonin 2C receptor in the pathophysiology of affective disorders and in the action of antidepressants. We analyzed the time course of 5-HT2C receptor (5-HTR2C) mRNA expression during antidepressant treatment in the prefrontal/frontal cortex (P/FC) and in the hippocampus (HC) of rats chronically treated with fluoxetine (a selective serotonin reuptake inhibitor) and reboxetine (a selective noradrenaline reuptake inhibitor). We also anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 101 publications
2
16
0
1
Order By: Relevance
“…Thus, the 5-HT system can control the neuronal activity of the LHb by acting through 5-HT 2C receptors. Several studies have found that 5-HT 2C receptor is involved in the regulation of depression-like behaviors and a potential target for antidepressant drug development (Kennett et al, 1994;Gurevich et al, 2002;Loo et al, 2002;Seretti et al, 2004;Dremencov et al, 2005;Barbon et al, 2011). However, at present, no clear evidence Fig.…”
Section: Depressive-like Behaviors Involve Increased Firing Activity mentioning
confidence: 98%
See 1 more Smart Citation
“…Thus, the 5-HT system can control the neuronal activity of the LHb by acting through 5-HT 2C receptors. Several studies have found that 5-HT 2C receptor is involved in the regulation of depression-like behaviors and a potential target for antidepressant drug development (Kennett et al, 1994;Gurevich et al, 2002;Loo et al, 2002;Seretti et al, 2004;Dremencov et al, 2005;Barbon et al, 2011). However, at present, no clear evidence Fig.…”
Section: Depressive-like Behaviors Involve Increased Firing Activity mentioning
confidence: 98%
“…Further, activation of 5-HT 2C receptors increases neuronal excitability in several brain regions (Barnes and Sharp, 1999). In addition, several studies have also shown the involvement of 5HT 2C receptors in depression (Gurevich et al, 2002;Seretti et al, 2004;Dremencov et al, 2005;Barbon et al, 2011).…”
Section: Introductionmentioning
confidence: 98%
“…The fully unedited 5-HT 2C receptor has high levels of constitutive activity (i.e., agonist-independent signaling) and strong coupling efficacy; as editing is increased, constitutive activity is diminished. Various editing patterns of the 5-HT 2C receptor are associated with depression (Gurevich et al, 2002), suicide (Gurevich et al, 2002;Niswender et al, 2001;Pandey et al, 2006;Dracheva et al, 2008b;Dracheva et al, 2008a) and schizophrenia (Sodhi et al, 2001) in humans, and these editing patterns are modulated by chronic antidepressant administration in both humans (Gurevich et al, 2002) and rodents (Barbon et al, 2011;Englander et al, 2005). It is not yet known if changes in mRNA editing of the 5-HT 2C receptor are involved in SUDs.…”
Section: Mirtazapine: Pharmacology Physiology and Behaviormentioning
confidence: 99%
“…Therefore, these processes must be explored in great detail when investigating changes in the editing levels of ADAR targets either during development [52][53][54], under pathological conditions [55,56] and in response to specific pharmacological treatments [57][58][59][60].…”
Section: Genomic Organization and Post-transcriptional Regulation Of mentioning
confidence: 99%